UFMylation: A Potential Modification for Neurological Diseases - Che, Guanglu; Xiao, Xiao; Li, Tingyu; Li, Jingdong; Gao, Linbo (Current Neuropharmacology, 2025)
Neurological disorders are the leading health threats worldwide, characterized by impairments in consciousness, cognition, movement, and sensation, and can even lead to death. UFMylation is a novel post-translational modification (PTM) that serves as an important regulatory factor, promoting the complexity of protein structures and enhancing the diversity and specificity of functions. In UFMylation, ubiquitin-fold modifier 1 (UFM1) is covalently transferred to the primary amine of a lysine residue on the target protein through the synergistic action of three enzymes: the activating enzyme E1 of UFM1, the coupling enzyme E2 of UFM1, and the ligase E3. UFMylation has been proven to be involved in various cellular processes, such as the maintenance of genome homeostasis, autophagy, signal transduction during antiviral responses, cell death, and differentiation. Additionally, a growing number of evidence suggests that polymorphisms in genes related to the UFMylation system are associated with the risk of epileptic encephalopathy, microcephaly, neurodegenerative diseases, and schizophrenia. Therefore, the concept, enzymatic cascade, and biological functions of UFMylation are carefully summarized, along with its potential role in neurological diseases.
Keywords: neurological diseases